2007
DOI: 10.1007/s12020-008-9037-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve after l-thyroxine therapy in Hashimoto’s thyroiditis patients with subclinical and overt hypothyroidism

Abstract: Subclinical as well as overt hypothyroid patients have impaired coronary microvascular function which improved after L: -thyroxine therapy. Treatment of Hashimoto's thyroiditis patients with subclinical hypothyroidism should be considered to improve cardiovascular disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…It should be noticed that treatment with levothyroxine (used to correct clinical hypothyroidism) signifi cantly aff ects a patient's infl ammatory profi le, reducing the pro-infl ammatory cytokines, increasing IL-10 levels, and lowering serum IgG concentrations ( 29,30 ). Levothyroxine therapy might therefore improve coronary microvascular function and thereby prevent cardiovascular events (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that treatment with levothyroxine (used to correct clinical hypothyroidism) signifi cantly aff ects a patient's infl ammatory profi le, reducing the pro-infl ammatory cytokines, increasing IL-10 levels, and lowering serum IgG concentrations ( 29,30 ). Levothyroxine therapy might therefore improve coronary microvascular function and thereby prevent cardiovascular events (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Oflaz et al (37) with a smaller group of subjects (18 SCH, 24 controls) and adenosine as a stimulus of hyperaemia-endothelium independent vasodilation obtained similar results for CFR (SCH 1.97 ± 0.09 vs. controls 2.58 ± 0.08.The same authors evaluated CFR for LAD before and after the introduction of levothyroxine replacement therapy and showed that there was a significant increase in CFR for LAD in SCH group after six month levothyroxine substitution (2.03 ± 0.13 vs 2.54 ± 0.18) but the study was conducted on only ten patients with SCH (38). Biondi et al (39) also showed a significant difference in CFR between the SCH and control group (SCH 20, control 15), but they induced endotheliumdependent vasodilation and hyperaemia using a cold pressor test as an inducer ( SCH 1.4 ± 0.2 vs. controls 1.9 ± 0.3 p< 0.0001) (39).…”
Section: Discussionmentioning
confidence: 76%
“…Some studies have shown that l -thyroxine treatment could improve coronary flow or reduce hyperlipidemia in patients with HT. 32 , 33 By contrast, another study reported that l -thyroxine treatment increased coagulation factor levels and inhibited fibrinolysis, increasing the risk of ischemic stroke. 34 In the present study, an insufficient period of l -thyroxine treatment affected the outcome, whereas l -thyroxine treatment reduced the risk of depression in Taiwan.…”
Section: Discussionmentioning
confidence: 97%